Quantitative assessment of the value of spirometry. Issue 5 (May 1986) - Russell, N J; Crichton, N J; Emerson, P A; Morgan, A D
Abstract : To determine the value of simple spirometric measurements in the diagnostic assessment of breathless patients, doctors requesting such tests were asked to predict the likely ventilatory abnormality, expressing these pretest predictions as probabilities. Comparison of these pretest predictions with the test results allowed an analysis of the doctors' ability to identify lung function abnormalities and an assessment of the diagnostic usefulness of the test. Predictions and spirometric measurements were made in 123 patients. Doctors expressed preference for a particular spirometric category in 112 cases, of which 13 were predicted to have a restrictive defect, 77 were predicted to have an obstructive defect, and 22 were predicted to be normal. Spirometry showed that nine patients had a restrictive defect, 79 had an obstructive defect, and 24 had normal indices. The study showed that 61% of the tests gave a result that doctors predicted as being unlikely. The study also showed that doctors had difficulty in identifying the reversibility of airflow obstruction in patients in whom they correctly predicted obstruction. Spirometry fulfils a useful role in the diagnosis of breathless patients.